Primary Yolk Sac Tumor in the Cerebellar Hemisphere: A Case Report and Literature Review of the Rare Tumor - Wu, Na; Chen, Qiang; Chen, Meng; Ning, Jinbo; Peng, Shulei; Zhang, Taotao; Zhong, Wen; Duan, Song; Cheng, Chongjie; Xie, Yimin (Frontiers in Oncology, 2021)
Yolk sac tumor (YST) is one of rare malignant germ cell tumors (GCTs). Primary intracranial YST, also endodermal sinus tumor (EST), is a quite rare type of brain tumor. Here, we report a case of YST, review the relevant literature, and propose a treatment strategy for this rare tumor. A 6-year-old boy initially manifested symptoms of dizziness and vomiting. Computed tomography (CT) and magnetic resonance imaging (MRI) showed a large irregular oval tumor in the cerebellar hemisphere. We subtotally removed the tumor by microsurgery through the left suboccipital approach. Immunohistochemical staining showed that alpha fetoprotein (AFP) was positive and the Ki-67 proliferation index was high (60%), suggesting a germ cell tumor. After 3 months of follow-up, neither recurrence of tumor nor complications were found in the patient. The diagnosis of YST should be confirmed on the basis of clinical manifestations, neuroimaging and pathological findings. Gross total resection (GTR) is an ideal treatment for YST. However, due to the location of the tumor, GTR is usually difficult, and the rate of postoperative complications is high. This reported case shows that subtotal resection can be a good treatment strategy for YST.